2020
DOI: 10.3389/fmicb.2020.00317
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Phthalate Plasticizers and Bisphenol A by Marine-Derived, Freshwater, and Terrestrial Fungi

Abstract: Phthalate esters (PEs, Phthalates) are environmentally ubiquitous as a result of their extensive use as plasticizers and additives in diverse consumer products. Considerable concern relates to their reported xenoestrogenicity and consequently, microbial-based attenuation of environmental PE concentrations is of interest to combat harmful downstream effects. Fungal PE catabolism has received less attention than that by bacteria, and particularly fungi dwelling within aquatic environments remain largely overlook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 92 publications
(211 reference statements)
1
8
0
2
Order By: Relevance
“…On the 15th day, SDBP4 degraded 99.34% of the DBP present in the medium, while SDBP6 could degrade only 29.44%, which showed distinct variability in DBP assimilation among the isolates. A study including different fungi: Ascocoryne sp., Phoma sp., Clavariopsis aquatica and Paradendryphiella arenariae also exhibited differences in the consumption of DBP, which supports our results [ 41 ]. Thus, SDBP4 was further identified at the molecular level due to its highest degradation capacity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the 15th day, SDBP4 degraded 99.34% of the DBP present in the medium, while SDBP6 could degrade only 29.44%, which showed distinct variability in DBP assimilation among the isolates. A study including different fungi: Ascocoryne sp., Phoma sp., Clavariopsis aquatica and Paradendryphiella arenariae also exhibited differences in the consumption of DBP, which supports our results [ 41 ]. Thus, SDBP4 was further identified at the molecular level due to its highest degradation capacity.…”
Section: Discussionsupporting
confidence: 91%
“…The medium was supplemented with DBP (50 mg L −1 ) from stock made with equal volumes of DBP and ethanol. Tween 80 (400 mg L −1 ) was added to the medium to improve DBP’s solubility [ 41 , 42 ]. The same medium composition was used for further degradation experiments.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the detoxification of penicillin side-chain precursors might depend on microsomal GST in P. chrysogenum (Emri et al, 2003). Fungal cytochromes can catalase a lot of different reactions, which enables them to degrade xenobiotics and pollutants (Syed et al, 2013;Chen et al, 2019;Wang et al, 2019;Carstens et al, 2020;Hu et al, 2020). Fungal enzymes, isolated from Basidiomycetes and Ascomycetes, show high ability of plastic waste biodegradation.…”
Section: Enzymatic Processesmentioning
confidence: 99%
“…These microorganisms may enhance pollutant degradation in phthalate-contaminated environments. Several investigations have revealed that fungal species such as Polyporus brumalis , Ganoderma lucidum , Trametes versicolor , Phlebia tremellosa , Neurospora sithopila , P. ostreatus , Phoma sp., Stropharia rugosoannulata , Ascocoryn e sp., Puccinia arenariae are phthalate-degrading organisms (Hwang et al, 2008 ; Kim et al, 2008 ; Lee et al, 2007 ; Kim & Song, 2009 ; Ahuactzin-Pérez et al., 2018a , 2018b ; Carstens et al, 2020 ; González-Márquez et al, 2019 ; González-Márquez et al, 2020 ; Hwang et al, 2012 ; Liao et al, 2012 ; Luo et al, 2012 ; Sánchez, 2021 ; Sánchez-Sánchez & Sánchez, 2019 ). In particular, fungi such as Fusarium species have been reported to degrade phthalates due to their esterase production.…”
Section: Introductionmentioning
confidence: 99%